Jersey : Financial Sector Assessment Program Update; Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Jersey's macroeconomic performance is generally satisfactory. Unemployment is low, and the trend growth rate and inflation have been satisfactorily examined. A Detailed Assessment of the Observance of the Basel Core Principles for Effective Banking Supervision Report on Jersey was also done. The legal system, which is broadly based on common law with French and Norman elements, is highly developed. The authorities have substantially adequate powers to direct, intervene in, and close a troubled financial institution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet